MEDIA’S CONTRIBUTION TO SOCIETY’S RESISTANCE AND EMPOWERMENT: A STUDY OF THE GOD OF SMALL THINGS - Vaid, Roshee (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the subjects of resistance and empowerment in Arundhati Roy's novel, The God of Small Things. The study examines how characters in the book challenge oppressive systems, defy societal norms, and navigate power structures. It analyzes instances where characters find strength and agency, breaking free from the constraints imposed by society. It also emphasizes the interconnectedness of the book and the role of media. It illustrates how media contributes to characters' empowerment and how empowerment fuels further resistance. The study highlights the complex relationship between these themes, demonstrating their individual and collective dimensions. Overall, the paper provides a comprehensive overview of the study's focus on resistance and empowerment in the selected novel shedding light on characters' efforts to navigate and transcend societal boundaries while seeking personal agency and empowerment.